2017
DOI: 10.1007/s00063-017-0278-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of lay rescuer chest compressions with a novel audiovisual feedback device

Abstract: The quality of CC carried out by laypeople is significantly improved with the use of a new feedback device. The device may be useful for cardiopulmonary resuscitation (CPR) by laypeople and for educational purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…More detailed information about characteristics and outcomes of included studies are also shown in S2 and S3 Tables in Supplementary materials. Among 42 studies included, 32 were RCTs, 6 studies [18,36,45,54,55,57] were randomized crossover controlled trials and 4 studies [24,48,49,53] were non-randomized studies. There were 13 studies conducted in North America [18,2224,34,35,37,40,44,49,52,53,58], 19 in Europe [17,2527,2931,33,38,39,4143,45,46,48,51,55,57], and 10 in the Asia-Pacific region [1921,28,32,36,47,50,54,56].…”
Section: Resultsmentioning
confidence: 99%
“…More detailed information about characteristics and outcomes of included studies are also shown in S2 and S3 Tables in Supplementary materials. Among 42 studies included, 32 were RCTs, 6 studies [18,36,45,54,55,57] were randomized crossover controlled trials and 4 studies [24,48,49,53] were non-randomized studies. There were 13 studies conducted in North America [18,2224,34,35,37,40,44,49,52,53,58], 19 in Europe [17,2527,2931,33,38,39,4143,45,46,48,51,55,57], and 10 in the Asia-Pacific region [1921,28,32,36,47,50,54,56].…”
Section: Resultsmentioning
confidence: 99%
“…The optimal percentage of adequate chest compression in laypersons is hard to define, but it ranged from 58.9% to 77.8% with a feedback device and from 14.6% to 66.6% without a feedback device, respectively in previous studies. 17,19 Apparently, the rates vary widely and could differ depending on the method of training and participants' characteristics. In our study, the percentage of adequate chest compression depth was 51.0% and 26.9% in the RTFG and NFG, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore there is also a need to use the quality of training to measure the user’s mastery of knowledge and skills. Many researchers have also validated the feasibility of their studies by measuring and comparing users’ knowledge skill mastery ( 52 , 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have delved into short-video production elements to enhance user attention, content absorption, and learning willingness, contributing to the widespread adoption of health education through short videos (53, 54). Additionally, experts have advocated the use of virtual simulation systems for first aid technology exercises and high-fidelity mannequins with audio-visual feedback devices for real-time training guidance, enhancing the quality of training (55)(56)(57).…”
Section: Public First Aid Toolmentioning
confidence: 99%